2021
DOI: 10.3389/fendo.2021.646233
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Exosomes as a New Strategy for the Treatment of Diabetes Complications

Abstract: Diabetes mellitus (DM) is a metabolic disease, now prevalent worldwide, which is characterized by a relative or absolute lack of insulin secretion leading to chronically increased blood glucose levels. Diabetic patients are often accompanied by multiple macrovascular complications, such as coronary heart disease, hypertension, macrovascular arteriosclerosis, and microvascular complications. Microvascular complications include diabetic kidney injury, diabetic encephalopathy, and diabetic foot, which reduce the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 117 publications
(126 reference statements)
0
58
0
Order By: Relevance
“…It has the characteristics of slow onset, long duration, and prolonged disease progression, which eventually leads to the loss of self-care ability and even death of patients. At present, clinical control of diabetes is mainly through medication, diet control, and insulin injection therapy, and a combination with symptomatic treatment to control diabetic complications, but the effect is still unsatisfactory ( 2 ). Therefore, there is an urgent need for new therapeutic interventions for DM and its complications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has the characteristics of slow onset, long duration, and prolonged disease progression, which eventually leads to the loss of self-care ability and even death of patients. At present, clinical control of diabetes is mainly through medication, diet control, and insulin injection therapy, and a combination with symptomatic treatment to control diabetic complications, but the effect is still unsatisfactory ( 2 ). Therefore, there is an urgent need for new therapeutic interventions for DM and its complications.…”
Section: Discussionmentioning
confidence: 99%
“…EVs are nanosized particles secreted by cells, which contain a variety of biologically active substances, such as lipids, proteins, and RNAs, and play an important role in intercellular communication, cell survival and apoptosis, and the regulation of disease progression. Interestingly, numerous previous studies have shown that SC-EVs, especially exosomes, have repairing effects similar to SCs without the risk of tumor formation and can be stably preserved for transport, which has attracted a great deal of attention from researchers ( 2 , 17 ). To explore the process and trend of SC-EVs for DM, this study conducted a bibliometric analysis of the publication on SC-EVs for DM from 2017 to 2021.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Type 2 diabetes mellitus (T2DM) is a complex metabolic disease which multiplies the likelihood of developing macrovascular complication, such as coronary artery diseases (CAD) and peripheral arterial disease (PAD) ( Shah et al, 2015 ; Joseph et al, 2020 ; Singh et al, 2021 ; Markousis-Mavrogenis et al, 2022 ), and microvascular complication, mainly nephropathy and retinopathy ( Altavilla et al, 2009 ; Saputro et al, 2021 ; Xiong et al, 2021 ; Markousis-Mavrogenis et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%